Novel Strategies and Approaches in Hypertension Therapy - Uzun, Hafize (Current and Future Developments in Hypertension Series., 2019)
Hypertension has become a major public health problem in the last few decades. High blood pressure is a serious risk factor for premature cardiovascular disease and end organ damage including left-ventricular hypertrophy and congestive heart failure, which in-turn increases the risk of cardiovascular morbidity and mortality. While studies of hypertension have been performed worldwide in a variety of epidemiological settings such as diabetes, renal function, obesity and thyroid disorders, there is a need to identify appropriate treatment strategies Novel Strategies and Approaches in Hypertensio.